Micro- and nanotechnology detection and delivery systems for screening and optimisation of MSC chondrogenesis for cartilage regeneration - Tay, Li Min (2018)
Cartilage regeneration remains a clinical challenge. Majority of clinical treatments for cartilage injuries and disorders mainly help to address related complications or postpone the need for joint replacement. Mesenchymal stem cells (MSCs) are looked upon as prospective cell source for cartilage regeneration due to its high proliferative and multipotency capabilities. There are several in vitro studies revolve around the use of different scaffold materials, physical cues, signaling molecules and growth factors to provide chondrogenic differentiation cues to MSCs. These studies often required the use of large amount of MSCs, materials and reagents for screening and validation of MSC chondrogenesis using the conventional methods. Nevertheless, with the combination of tissue engineering and micro- and nanotechnology, it will represent a more efficient system for the study of MSC chondrogenesis for cartilage regeneration. In this thesis, we focus on developing detecting system with nanosensors to screen optimal chondrogenic conditions to attain proliferative chondrocytes for cartilage regeneration. At the same time, we explored into creating a controlled-release delivery system with ultrasound-activated magnetic microbubbles in three-dimensional (3D) construct for future growth factor delivery Firstly, in chapter 2, we introduced the use of modified polymer chains to fabricate nanosenosrs for real-time cell tracking. In particular, di(thiophene-2-yl)-diketopyrrolopyrrole (DPP) was inserted in between two polycaprolactone (PCL) polymer chain through covalent bond, in which it was used to synthesis PCL-DPP-PCL NPs. We were able to monitor MSCs for 28 days and it showed no adverse effects these nanosensors have on MSC adipogenic and chondrogenic. While these nanosensors have the advantage of long-term tracking of MSC, molecular beacon (MB)-based nanosensors have additional advantage of noninvasively monitor target intracellular mRNA expression, which will be elaborated in chapter 3. We have demonstrated the potential of MB-NPs as a platform to observe the type II collagen (Col2) expression over a period of 28 days in MSCs embedded in 3D agarose when induced with chondrogenic medium. There was also a good correlation between the Col2 trend observed with MB-NPs and qRT-PCR data. Chapter 4 further explored this detection platform. It was utilised to screen the optimal time point to add fibroblast growth factors (FGF2) to attain proliferative chondrocytes. High expression of Col2 and Ki67 were observed when FGF2 was added from days 14 to 20, with the treatment of TGFβ3 from days 0 to 13 and days 21 to 28. The fluorescence signal trend of both Col2 and Ki67 MBs coincided with quantitative real-time polymerase chain reaction (qRT-PCR) data. Future screening of MSC chondrogenic conditions for cartilage regeneration can thus be realised through the use of this nanosensor platform. Lastly, we developed a controlled-release system in 3D construct with magnetic microbubble technology. We were able to coat different cargos onto the magnetic microbubbles and released in 3D construct under ultrasound stimulation. These combination techniques bring about a promising system for cartilage regeneration in the near future.